Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.4082/kjfm.18.0113
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Prognosis Awareness on the Survival and Quality of Life of Terminally Ill Cancer Patients: A Prospective Cohort Study

Abstract: Background: Physicians and caregivers are conflicted over whether to inform patients that their disease is terminal. Studies examining the effect of awareness of prognosis on the survival and quality of life of terminally ill cancer patients report conflicting results. This study aimed to assess the effects of prognosis awareness on the survival time and psychological health of terminally ill cancer patients. Methods: Patients in the hospice wards of two general hospitals were asked to complete a questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 34 publications
(42 reference statements)
1
17
0
Order By: Relevance
“…We assessed the quality of the 32 quantitative studies as high in 12 studies, [24][25][26][27][28][29][30][31][32][33][34][35] moderate in 9, [36][37][38][39][40][41][42][43] and low in 11. [44][45][46][47][48][49][50][51][52][53][54] We assessed the quality of the six qualitative studies as high in four, [55][56][57][58] and moderate in two.…”
Section: Methodological Qualitymentioning
confidence: 99%
“…We assessed the quality of the 32 quantitative studies as high in 12 studies, [24][25][26][27][28][29][30][31][32][33][34][35] moderate in 9, [36][37][38][39][40][41][42][43] and low in 11. [44][45][46][47][48][49][50][51][52][53][54] We assessed the quality of the six qualitative studies as high in four, [55][56][57][58] and moderate in two.…”
Section: Methodological Qualitymentioning
confidence: 99%
“…Semi-structured interviews were used in seven studies. 9,14,[30][31][32][33][34] Please see Supplemental Materials, Supplemental Table C for a summary of the questions used in semi-structured interviews. The method of how prognostic awareness was measured was not reported in one study.…”
Section: Measurement and Definition Of Prognostic Awarenessmentioning
confidence: 99%
“…In several studies, it has been found that conspiracy of silence and false hope lead the patients seeking aggressive but non-beneficial treatments. Both of these have a negative consequence on the patients' quality of life [29][30][31]. We did not explore the exact reason behind this contradiction.…”
Section: Plos Onementioning
confidence: 99%